Sublethal effects of chlorantraniliprole on growth, biochemical and molecular parameters in two chironomids, Chironomus kiiensis and Chironomus javanus - Yanhui Lu; Xusong Zheng; Xiaochan He; Jiawen Guo; Qiming Fu; Hongxing Xu; Zhongxian Lu (Ecotoxicology and Environmental Safety, 2023)
Pesticide residues have serious environmental impacts on rice-based ecosystems. In rice fields, Chironomus kiiensis and Chironomus javanus provide alternative food sources to predatory natural enemies of rice insect pests, especially when pests are low. Chlorantraniliprole is a substitute for older classes of insecticides and has been used extensively to control rice pests. To determine the ecological risks of chlorantraniliprole in rice fields, we evaluated its toxic effects on certain growth, biochemical and molecular parameters in these two chironomids. The toxicity tests were performed by exposing third-instar larvae to a range of concentrations of chlorantraniliprole. LC50 values at 24 h, 48 h, and 10 days showed that chlorantraniliprole was more toxic to C. javanus than to C. kiiensis. Chlorantraniliprole significantly prolonged the larval growth duration, inhibited pupation and emergence, and decreased egg numbers of C. kiiensis and C. javanus at sublethal dosages (LC10 = 1.50 mg/L and LC25 = 3.00 mg/L for C. kiiensis; LC10 = 0.25 mg/L and LC25 = 0.50 mg/L for C. javanus). Sublethal exposure to chlorantraniliprole significantly decreased the activity of the detoxification enzymes carboxylesterase (CarE) and glutathione S-transferases (GSTs) in both C. kiiensis and C. javanus. Sublethal exposure to chlorantraniliprole also markedly inhibited the activity of the antioxidant enzyme peroxidase (POD) in C. kiiensis and POD and catalase (CAT) in C. javanus. Expression levels of 12 genes revealed that detoxification and antioxidant abilities were affected by sublethal exposures to chlorantraniliprole. There were significant changes in the expression levels of seven genes (CarE6, CYP9AU1, CYP6FV2, GSTo1, GSTs1, GSTd2, and POD) in C. kiiensis and ten genes (CarE6, CYP9AU1, CYP6FV2, GSTo1, GSTs1, GSTd2, GSTu1, GSTu2, CAT, and POD) in C. javanus. These results provide a comprehensive overview of the differences in chlorantraniliprole toxicity to chironomids, indicating that C. javanus is more susceptible and suitable as an indicator for ecological risk assessment in rice ecosystems.